Strategi Naratif Dan Visualisasi Sejarah Kepada Wisatawan Gen Z - Suesilowati, Suesilowati; Juliyanti, Salsa Billa; Aurelie, Ellen (International Journal on Advanced Science, Education, and Religion, 2025)
This research explores the application of narrative strategies and the use of visual media in presenting history by guides at the Jakarta History Museum to Generation Z visitors. The study is motivated by the low level of interest among Gen Z in visiting museums, often due to the rigid delivery of information and the limited use of interactive media. A descriptive qualitative approach was applied, with data collected through in-depth interview and documentation. The findings indicate that museum guides tend to combine chronological and thematic flows, include stories of historical figures, and adopt a casual tone familiar to younger audiences, occasionally interspersed with popular culture references. Visual support such as immersive rooms, interactive maps, and AR/VR technology proved effective in clarifying historical content while increasing visitor engagement. This study highlights that blending relevant storytelling with interactive visual media serves as an effective communication approach to foster young generations’ interest in history